2022
DOI: 10.1002/pd.6276
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive prenatal screening for cystic fibrosis using circulating trophoblasts: Detection of the 50 most common disease‐causing variants

Abstract: Objectives: Cystic fibrosis (CF) is one of the most common severe autosomal recessive disorders. Prenatal or preconception CF screening is offered in some countries. A maternal blood sample in early pregnancy can provide circulating trophoblasts and offers a DNA source for genetic analysis of both the mother and the fetus. This study aimed to develop a cell-based noninvasive prenatal test (NIPT) to screen for the 50 most common CF variants.Methods: Blood samples were collected from 30 pregnancies undergoing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Another strength of cbNIPT over cfNIPT is that the same blood sample used for aneuploidy and CNV detection can potentially be used for prenatal screening of monogenic disorders 13 . We have found that cbNIPT can also be used for screening for cystic fibrosis 13 and we are currently validating other monogenetic disorders in the same setup.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Another strength of cbNIPT over cfNIPT is that the same blood sample used for aneuploidy and CNV detection can potentially be used for prenatal screening of monogenic disorders 13 . We have found that cbNIPT can also be used for screening for cystic fibrosis 13 and we are currently validating other monogenetic disorders in the same setup.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, they constitute an attractive source for non-invasive prenatal testing for aneuploidies, sex chromosome aberrations (SCA), and pathogenic CNVs, [8][9][10][11][12] as well as monogenic disorders. 13 For example, whole genome amplification from 3 harvested fetal cells rendered enough DNA for both chromosomal microarray (CMA) and cystic fibrosis screening. 13 This provides a future opportunity for a wider screening using a blood sample only from the pregnant women without the need for partner samples.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell-free fetal nucleic acids are accompanied by a low number of fetal cells in the maternal bloodstream, namely trophoblastic cells derived from the placental tissue and early erythrocytes (i.e., red blood cells), which are also specific to the ongoing pregnancy [138,139] . These populations of cells can theoretically be isolated from peripheral maternal blood from as early as 6 weeks of pregnancy, although reportedly more reliably from 10-14 weeks, and offer a source of intact fetal chromosomal DNA for NIPD of monogenic conditions [140][141][142][143] . Obtaining a pure fetal cell population provides the benefit of having intact gDNA within which more complex pathogenic variants can be detected [144] , such as triplet repeat expansions [145] .…”
Section: Cell-based Nipdmentioning
confidence: 99%